Contribution à l’inventaire des zooplanctons dans le barrage d’Oued Charef ( Souk - Ahras ) - Louabdia Imen; Tayebi Soumia (My University, 2018)
The physicochemical parameter and the contribution of the zooplankton inventory were studied and bird counts monitored. the three Zoo-planktonic groups (Copepods Cladocerans and Rotifers) with a more marked species diversity: Copepods dominate throughout the stations and all the months with 80% followed by Cladocere 16% which are present during the entire prospecting period are extremely abundant during the month of March, Rotifers almost decrease during the study period with 4% The distribution of the zoo-planktonic community is influenced by physicochemical and climatic parameters, The spatial and temporal distribution of zooplankton depends on the ecological conditions of the middle. ------------------------------------------------------------------------------------------- تمت دراسة العوامل الفيزيوكيميائية ومساهمة مخزون العوالق الحيوانية وتم رصد تعداد الطيور. مجموعات العوالق الحيوانية الثلاث (مجدافيات الأرجل، وكلادوسيرا، وروتيفيرا) مع تنوع أكثر وضوحًا في الأنواع: تهيمن مجدافيات الأرجل في جميع المحطات وكل الأشهر بنسبة 80% تليها كلادوسيرا 16% الموجودة خلال فترة المسح بأكملها تكون وفيرة للغاية خلال شهر مارس، وتتناقص الروتيفر تقريبًا خلال فترة الدراسة بنسبة 4%، ويتأثر توزيع مجتمع العوالق الحيوانية بالعوامل الفيزيائية والكيميائية والمناخية، والزمانية المكانية. يعتمد توزيع العوالق الحيوانية على الظروف البيئية للبيئة. --------------------------------------------------------------------------------------------- On a étudié les paramètres physicochimiques et la contribution de l’inventaire de zooplancton et suivi le dénombrement des oiseaux. les trois groupes Zoo-planctonique (Copépodes, Cladocères et Rotifères) avec une diversité en espèce plus marqué: les Copépodes dominent dans tout les station et tout les mois avec 80% suivi par les Cladocère 16 % qui sont présent pendant toute la période de prospection sont extrêmement abondante pendant le moi de Mars, les Rotifère presque diminue pendant la période d’études avec4%.la distribution de la communauté zoo-planctonique est influencé par les paramètres physicochimique et climatique, La répartition spatiotemporelle des zooplanctons dépend des conditions écologiques du milieu.